Radiology’s Role in the Detection and Management of Long-Term Complications Associated with COVID-19: A Comprehensive Review - Alshammary, Amjad Sulaiman; Alshammari , Wesam Faiz; Alanzi , Reem Shleweh; Alsalhani, Miad Azooz; Mutabi , Yusra Abdullah; Mujarribi, Reem Yahya; Al-Otaibi, Khaled Break Naqa (Journal of Ecohumanism, 2024)
The ongoing COVID-19 pandemic, caused by the SARS-CoV-2 virus, has led to significant challenges in healthcare systems worldwide. Beyond acute respiratory symptoms, many patients experience long-term complications, often termed "long COVID." Radiology plays a crucial role in identifying and managing these complications, allowing for timely interventions and improved patient outcomes.This review examines the current literature on the use of various radiological modalities, including chest X-rays (CXR), computed tomography (CT), and lung ultrasonography (LUS), in detecting and assessing COVID-19-related pulmonary complications. A comprehensive analysis of imaging findings and their correlation with clinical outcomes was performed, drawing from multiple studies that highlight the efficacy and limitations of these imaging techniques.The findings indicate that while CT is highly sensitive in diagnosing COVID-19 pneumonia, CXR remains a valuable initial imaging tool, especially in emergency settings. LUS has emerged as a useful bedside alternative, particularly in critically ill patients. Each modality presents unique advantages and limitations, with varying efficacy in different clinical contexts. Scoring systems for assessing the severity of pulmonary involvement were also reviewed, emphasizing the importance of standardized reporting in clinical practice.Radiological imaging is integral to the detection and management of long COVID-19 complications. Combining multiple imaging modalities can enhance diagnostic accuracy and facilitate better patient care. Future research should focus on refining imaging protocols and establishing guidelines for the effective use of radiology in managing long COVID-19.